Contemporary research on management and business : proceedings of the International Seminar of Contemporary Research on Business and Management (ISCRBM 2021), 18 December 2021, Jakarta, Indonesia /: proceedings of the International Seminar of Contemporary Research on Business and Management (ISCRBM 2021), 18 December 2021, Jakarta, Indonesia. (2022) - Unknown
No abstract available